IMPLEMENTINGACOMPREHENSIVEAPPROACHTOHEALTHCAREDELIVERY FOR ENHANCED PATIENT OUTCOMES IN THE INTERSECTION OF NURSING, PHARMACY, AND PATIENT WELLNESS - Saleh Ali Saleh Aljawad HatimRabeeHatimAlmansou Mahdi Faris Saeed Alyami YahyaHadiHamadAlGorea MohammedHoussainAlmansour MohammedSalehMohammedAlKumsan ManeaSalehMisferAlMordef MahdiKhadeishNasserAlKhadeish (Chelonian Research Foundation, 2023)
This article investigates the implementation of an integrated healthcare framework, emphasizing the crossing point of care, pharmacy, and patient well-being. Through a writing survey, this articleexploresthecollaborationbetweenthesedisciplinesandtheireffectonpatientresults. Techniques for integrating nursing, pharmacy, and calm well-being into healthcare administrationsandinquiriesaboutanddiscoveriesaboutthisstrategy'sbenefitsarediscussed The talk highlights the challenges and openings related to collaborative organizations and offers recommendations for creating this show in healthcare. This article highlights the significance ofa positive approach to understanding care that addresses physical, enthusiastic, and mentalhealth. Keywords: Healthcare delivery, nursing, pharmacy, patient wellness, interdisciplinary collaboration, patient outcomes